The effect of quick on the draw strategy on critical thinking skills of grade IV - Yuniar Nur Adinda; Nyamik Rahayu Sesanti; I Ketut Suastika (Lembaga Pengembangan Pendidikan dan Pembelajaran, Universitas Negeri Malang in Collaboration with Asosiasi Pendidik dan Pengembang Pendidikan Indonesia (APPI), 2025)
This study aims to determine whether the critical thinking skills of fourth-grade students are influenced by the application of Quick On The Draw-based learning strategies. This research methodology uses a quantitative approach with a quasi-experimental research design. The experimental class and control class received two different treatments as part of the Quasi Experiment Design research design. This study used two tests, namely validity and reliability tests needed to evaluate the test instrument. In addition, this study also used normality tests, homogeneity tests, and hypothesis tests. Of the three tests, the hypothesis test is the most important data analysis test used to determine whether the Quick On The Draw strategy affects students' critical thinking skills. Where the results of the hypothesis test show that Ha is accepted or there is an effect of the Quick On The Draw strategy on students' critical thinking skills, in addition to hypothesis testing, the impact of this strategy can also be seen through the average value of students which results in a difference in the average value of the experimental class of 78.23% and the average value of the control class of 58.23%, so there is a difference of 20% between the two sets of data.